Analysis of Factors Affecting Foreign Exchange Reserves in Indonesia (2017-2021) - Suripto Suripto; Nurmalinda Novayadi; Lestari Sukarniati; Mahrus Lutfi Adi Kurniawan (International Journal of Applied Business and International Management, 2023)
Foreign exchange reserves to maintain currency stability, finance international transactions, provide guarantees against global financial crises, strengthen national credibility, and provide financial flexibility. High foreign exchange reserves will have an impact on the implementation of economic policies to stabilize the domestic currency, diversify the economy, increase competitiveness, and good management of the balance of payments; the state can reduce the risk of a shortage of foreign exchange reserves and the negative impacts that may occur. This study aims to analyze the model of foreign exchange reserves in Indonesia. Variables that affect foreign exchange reserves are the exchange rate, exports, the BI rate, and the consumer price index. The VECM (Vector Error Correction Model) approach estimates the model. This study uses secondary time series data in the form of months from January 2017 to December 2021. The research findings are that the consumer price index has a significant positive effect in the short term, while the consumer price index at lag 3 has a significant negative impact. The exchange rate on lag one and lag 3 has no significant adverse effect, but on lag 2, it has a negative and significant impact. The export variable has a negative and significant effect on the three lags. Variable bit rate on lag one and lag 2 has no significant adverse effect, while lag 3 has a negative and significant impact. In the long term, the exchange rate and consumer price index variables substantially affect foreign exchange reserves. The BI rate variable has no significant effect on foreign exchange reserves, while exports significantly adversely impact foreign exchange reserves.